A multi-stable isotopic constraint on water column oxygen sinks in the Pearl River Estuary, South China. (June 2022) - Ye, Feng; Jia, Guodong; Wei, Gangjian; Guo, Wei
Abstract: Bottom water oxygen depletion is a central concern in estuaries and coastal oceans worldwide. However, a mechanistic understanding and quantitative diagnosis of different oxygen-consuming processes are less clear. In this study, a multi-stable isotope approach is developed to delineate the role of oxygen respiration and nitrification contributing to total oxygen consumption in the Pearl River Estuary (PRE), a large eutrophic estuary in south China. The approach highly couples with analysis of the carbon isotope composition of dissolved inorganic carbon (δ 13 C-DIC) and with stable nitrogen isotope analysis in ammonium (δ 15 N- N H 4 + ) and nitrate (δ 15 N- N O 3 − ). In all seasons, relatively low DO concentrations were observed in the upper reach and, to some extent, in the outer estuary during summer, while high concentrations of DO were found in the transition zone between the inner and outer estuary. On the basis of isotopic differentiation, our data reveal that much more depleted δ 13 C-DIC is coincident with DIC additions and low oxygen in the upper reach and inner estuary during most seasons. This is most likely a consequence of organic carbon (OC) degradation via aerobic respiration. Based on the carbon isotopic mass balance of DIC and the stoichiometry ratio of − Δ DO / Δ DIC, we found that the OC degradation dominates the total oxygen consumption in the upper reach, as well as in the inner estuary during summer (48.3%–93.5%). In addition, nitrification is another key process in contributing to total oxygen loss in the upper reach, as supported by the well-coupled variations of δ 15 N of N H 4 + and N O 3 − and apparent oxygen utilization (AOU). Using the formerly determined N isotopic fractionation and observed δ 15 N variation, we estimated that nitrification could account for 35.3%–44.1% and 28.5%–31.6% of the total oxygen consumption in the upper reach during winter and summer, respectively, while its contribution to total oxygen loss is minor in the inner and outer estuary. Overall, this study demonstrates the potential of the multi-stable isotopic approach to assess oxygen sink partitioning in large human-perturbed estuaries. Highlights: A multi-stable isotope approach is developed to delineate the role of oxygen respiration and nitrification contributing to oxygen depletion in the Pearl River Estuary. Organic carbon degradation dominates the total oxygen consumption in winter and summer. Nitrification is another key process in contributing to oxygen depletion in low salinity waters.